Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/ijerph18031081
|View full text |Cite
|
Sign up to set email alerts
|

IL-17F Gene rs763780 and IL-17A rs2275913 Polymorphisms in Patients with Periodontitis

Abstract: Background: Periodontitis (PD) is a chronic inflammatory disease that can eventually lead to tooth loss. Genetic and environmental factors such as smoking are involved in the pathogenesis of PD. The development of PD is potentiated by various pathogens that induce an immune response leading to the production of cytokines, such as interleukin (IL)-17. The synthesis of IL-17 is influenced genetically. The polymorphisms in IL-17 gene may affect the synthesis of IL-17. The aim of this study was to examine the asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…In agreement with Pedia snipe data, the authors found IL-17A (rs2275913) A allele was lower than G allele (29.2% and 70.8% respectively), and AA genotype was the lowest genotype (10/60, 16.7%) in leprosy patient group. Recently, Mazurek-Mochol et al 21 reported that the A allele was associated with increased production of IL-17. Therefore, decreased IL-17A (rs2275913) A allele and AA genotype in the present studied cases could also explain that difference.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with Pedia snipe data, the authors found IL-17A (rs2275913) A allele was lower than G allele (29.2% and 70.8% respectively), and AA genotype was the lowest genotype (10/60, 16.7%) in leprosy patient group. Recently, Mazurek-Mochol et al 21 reported that the A allele was associated with increased production of IL-17. Therefore, decreased IL-17A (rs2275913) A allele and AA genotype in the present studied cases could also explain that difference.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the IL17A gene variant has been linked to an increased risk of colorectal cancer in Asians and Caucasians [86,87], osteoarthritis in Caucasians [88], IgA nephropathy in Chinese Hans [89], polycystic ovarian syndrome in Chinese people [90], diabetic nephropathy in Iranians [91], diverse cancer in Asians [92], preeclampsia in Chinese people [93], and rheumatoid arthritis in Europeans [94]. However, IL17A polymorphism has been reported to show no association with many diseases, such as European and Asian psoriasis [95], Egyptian multiple myeloma [96], and Polish periodontitis [97].…”
Section: Discussionmentioning
confidence: 99%
“…The expression of these interleukins can be modified by polymorphisms in the IL-17 gene. Polymorphisms in IL-17 interleukins have been analysed in many inflammation-related diseases, autoimmune diseases and cancers [15][16][17][18][19][20][21]. The following were most commonly analysed: rheumatoid arthritis, psoriasis, ulcerative colitis, osteoarthritis, and asthma.…”
Section: Introductionmentioning
confidence: 99%